The Deubiquitinating Enzyme OTUD5 Sustains Inflammatory Cytokine Response in Inflammatory Bowel Disease. (7th July 2021) - Dinallo, Vincenzo; Di Fusco, Davide; Di Grazia, Antonio; Laudisi, Federica; Troncone, Edoardo; Di Maggio, Giulia; Franzè, Eleonora; Marafini, Irene; Colantoni, Alfredo; Ortenzi, Angela; Stolfi, Carmine; Di Daniele, Nicola; et al.
Abstract: Background and Aims: The inflammatory bowel disease [IBD]-associated immune response is marked by excessive production of a variety of inflammatory cytokines, which are supposed to sustain and amplify the pathological process. OTUD5 is a deubiquitinating enzyme, which regulates cytokine production by both innate and adaptive immune cells. Here, we investigated the expression and role of OTUD5 in IBD. Methods: OTUD5 expression was evaluated in mucosal samples of patients with Crohn's disease [CD], patients with ulcerative colitis [UC], and controls, as well as in mice with trinitrobenzene-sulphonic acid [TNBS]-induced colitis by real-time polymerase chain reaction, western blotting, immunohistochemistry, and immunofluorescence. Moreover, OTUD5 was assessed in lamina propria mononuclear cells [LPMC] stimulated with inflammatory cytokines. TNF-α, IL-6, and IL-10 were evaluated in LPMCs of IBD patients and in colitic mice transfected with a specific OTUD5 antisense oligonucleotide [AS]. Results: OTUD5 protein, but not RNA, expression was increased in inflamed ileal and colonic mucosal samples of patients with CD and patients with UC as compared with controls. In IBD, OTUD5-expressing cells were abundant in both epithelial and lamina propria compartments, and non-CD3+, HLA-DR+ LPMC were one of the major sources of the protein. OTUD5 expression was enhanced by IFN-γ through a p38/MAPK-dependent mechanism, and the AS-induced knockdown of OTUD5 in LPMCs of IBD patients and colitic mice reduced TNF-α. Conclusions: Our data show that OTUD5 is overexpressed in both CD and UC and suggest the involvement of such a protein in the amplification of the aberrant cytokine response in IBD.